'It is not only an artist village, it is much more than that'1. The binding and dividing effects of the arts on a community. (27th November 2017) - van der Vaart, Gwenda; van Hoven, Bettina; Huigen, Paulus P P
Abstract: The value of 'the arts' in community development is increasingly being recognized. This paper contributes to emerging insights on the various impacts of the arts on communities by highlighting when and how they can have binding and dividing effects on a community. We draw on a participatory research project conducted in Pingjum, a village in the Netherlands that hosts many cultural activities and in which many artists live. We discuss how the arts in Pingjum influence the community in the village. In our discussion, we pay attention to the sense of community that the arts generate, the meeting opportunities they provide and how the community is engaged by some artists. Our study shows that the influence of the arts is context-dependent, with the arts having both binding and dividing effects on the community in Pingjum. In terms of the value of the arts for community development, we emphasize three key issues: that the arts (i) do not have only advantages for a community; (ii) do not engage the entire community; and (iii) could potentially contribute to community fragmentation. Given these issues, we argue that the arts should be considered as one of several supportive means in community development processes. Ideally, they are integrated into a wider community development strategy and planning, and exist alongside other associations and activities in a community. In this way, the arts can contribute to the robustness of a community and assist it in developing the capacity and resources to flourish.